The impact of the European School of Oncology masterclass in clinical oncology on self-professional development. (July 2020) - Pavlidis, Nicholas; Peccatori, Fedro A.; Aapro, Matti; Eniu, Alex; Kay, Stanley; Rolfo, Christian; Cavalli, Franco; Costa, Alberto
Abstract: We investigated the impact of the European School of Oncology's (ESO) Masterclass (MCO) in Clinical Oncology on the career development of young participants. MCO represents the flagship educational activity of ESO and is organized annually, mostly in collaboration with the European Society for Medical Oncology (ESMO) in five different geographical regions. A questionnaire consisting of 21 questions was sent to all doctors who attended the ESO MCOs from 2009 to 2016. The 228 responders were mostly from European countries and hold the specialty of Medical Oncology. Ninety-five percent of them evaluated ESO MCOs as "extremely useful" or "useful" for their professional career. Around 60% were trained at University Hospitals or Cancer Institutes and currently, one-third of them are employed in Academic Centers. Eighty percent have performed translational or clinical research and 77.5% were able to publish in pertinent international journals. The contribution of ESO MCOs to trainees' career development in different oncology disciplines around the world is discussed.